Factors Associated with Atopic Dermatitis and Allergic Rhinitis among Residents of Two Municipal Areas in South Korea - Dilaram Acharya; Bishnu Bahadur Bajgain; Seok-Ju Yoo (Medicina, 2019)
Background and Objectives: The growing burden and deleterious health consequences of allergic diseases, especially of allergic rhinitis (AR) and atopic dermatitis (AD), in developed countries remains an important public health issue. The current study aimed to assess the prevalence and to identify the risk factors of atopic dermatitis and allergic rhinitis among residents of Pohang-Si and Yeongdeok-Gun, two municipal areas in South Korea. Materials and Methods: A cross-sectional study was conducted in both municipal areas between 12 November and 13 December 2017. A total of 302 subjects were recruited from 100 households (25 apartments and 25 houses in each municipality), by system extraction according to district code numbers. Data were collected using International Study of Asthma and Allergies in Childhood (ISAAC) Standard Questionnaires for children and a health questionnaire for adults. Risk factors were identified by multivariate logistic regression analysis. Results: Of the 302 study participants, 12.9% and 25.5% had AD and AR, respectively. The significant factors associated with AD by multivariate logistic regression analysis were age ≥19 years (aOR (adjusted odds ratio) 6.9; 95% CI (confidence interval) (2.9–16.37)), residence in Pohang-Si (aOR 2.5; 95% CI (1.18–5.53)), and family history of allergic disease (aOR 2.3; 95% CI (1.09–4.9)). Similarly, the significant factors associated with AR were male gender (aOR 2.3; 95% CI (1.24–4.42)), age ≥19 years (aOR 4.4; 95% CI (2.28–8.48)), residence in Pohang-Si (aOR 2.8; 95% CI (1.51–5.37)), and family history of allergic disease (aOR 6.7; 95% CI (3.50–12.82)). Conclusion: The present study shows that age ≥19 years, residence in Pohang-Si, and family history of allergic disease are risk factors for AD and AR, and that, additionally, male gender is a risk factor of AR. Understanding the risk factors of allergic diseases can aid the design and implementation of evidence-specific strategies to reduce the long-standing problems associated with allergic disease.